2003
DOI: 10.1175/1520-0426(2003)020<1449:wirtiw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Whitening in Range to Improve Weather Radar Spectral Moment Estimates. Part II: Experimental Evaluation

Abstract: Demonstration of a method for improved Doppler spectral moment estimation is made on NOAA's research and development Weather Surveillance Radar-1988 Doppler (WSR-88D) in Norman, Oklahoma. Time series data have been recorded using a commercial processor and digital receiver whereby the sampling frequency is several times larger than the reciprocal of the transmitted pulse width. The in-phase and quadrature-phase components of oversampled weather signals are used to estimate the first three spectral moments by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…It is shown that oversampling range samples using a wideband receiver and subsequently whitening the range samples would provide estimates with minimum error for any spectral moments in agreement with the results of Ivic et al (2003). It is shown that oversampling range samples using a wideband receiver and subsequently whitening the range samples would provide estimates with minimum error for any spectral moments in agreement with the results of Ivic et al (2003).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is shown that oversampling range samples using a wideband receiver and subsequently whitening the range samples would provide estimates with minimum error for any spectral moments in agreement with the results of Ivic et al (2003). It is shown that oversampling range samples using a wideband receiver and subsequently whitening the range samples would provide estimates with minimum error for any spectral moments in agreement with the results of Ivic et al (2003).…”
Section: Discussionsupporting
confidence: 63%
“…Computation of the transformation matrix from a real correlation matrix has also been suggested by Ivic et al (2003). The whitening transformation matrix is computed by using the magnitude of the correlation functions.…”
Section: January 2007 C H O U D H U R Y a N D C H A N D R A S E K A Rmentioning
confidence: 99%
“…Full utilization of fine-resolution data would require a technique for reducing the variance of the parameter estimates. One promising technique is the range oversampling and whitening approach proposed by Torres and Zrnić (2003) and evaluated by Ivić et al (2003). The technique works by oversampling in range-that is, by acquiring many samples within a range cell, and then manipulating these samples such that they become decorrelated.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Figure 1 shows the normalized standard errors of WTB, MFB, and OAB (a) differential reflectivity, (b) differential phase, and (c) cross-correlation coefficient estimators as a function of the SNR for the ideal case, a normalized spectrum width of 0.08, and true Z DR of 1 dB and HV of 0.98, which are representative of pure rain (Straka et al 2000). The oversampling factor L ϭ 8 is a realistic value that can be achieved on weather surveillance radar (Ivic et al 2003). When compared to MFB (or OAB) estimates, WTB estimates exhibit a superior performance for large SNR.…”
Section: Magnitude Of Zero-lag Cross-correlation Coefficient Estimmentioning
confidence: 99%